Empirical Analysis of Mining Costs Amid Energy Price Volatility for Secondary Deposits in Quarrying - Michał Patyk; Przemysław Bodziony (Energies, 2024)
The outlined methodology for calculating operating costs in open-cast mines and quarries not only facilitates the selection of optimal mining equipment and systems for working lower-grade secondary deposits but also adds significant value in navigating the challenges of fluctuating prices of energy carriers and fuels. Moreover, the study rigorously assesses the impact of mining operations on the performance of deployed mining equipment and the overall viability of the rock mining project. The selection procedure relies on a comprehensive analysis of the technical and economic parameters of selected solutions, providing critical insights to guide decisions regarding the continuation or discontinuation of mining operations. We analyse, based on empirical data, the technical and economic parameters of several variants of mining equipment to be used for the extraction of rocks and stones from secondary deposits in conditions of fluctuation depending on the level of energy prices, in order to find the best configuration in terms of operating costs and potential revenue. In addition to analysing the structure of operating costs, the article presents their correlation with the required profit from the sale of raw materials using the linear correlation method. The results clearly demonstrate the economic viability of mining secondary deposits, taking into account the actual costs incurred by mining companies.